2019
DOI: 10.3389/fimmu.2019.02890
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Response to Ozone

Abstract: The respiratory effects of O3 are well established. High ambient O3 concentrations are associated with respiratory symptoms, declines in pulmonary function, asthma exacerbations, and even mortality. The metabolic effects of O3 are less well appreciated. Here we review data indicating that O3 exposure leads to glucose intolerance and hyperlipidemia, characteristics of the metabolic syndrome. We also review the role of stress hormones in these events. We describe how the metabolic effects of O3, including effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 72 publications
0
11
0
1
Order By: Relevance
“…The adverse effect of O 3 on cardiovascular diseases has been also well established (Bourdrel et al 2017; Manisalidis et al 2020; Song et al 2020). However, the impact of this pollutant on metabolic alterations is less understood, even when the metabolic-impairment effects of O 3 have been determined in humans (Shore 2019). In this context, our results demonstrated that O 3 exposure had a significant effect on the regulation of the expression of certain adipokines and metabolic proteins that are linked to metabolic disease (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse effect of O 3 on cardiovascular diseases has been also well established (Bourdrel et al 2017; Manisalidis et al 2020; Song et al 2020). However, the impact of this pollutant on metabolic alterations is less understood, even when the metabolic-impairment effects of O 3 have been determined in humans (Shore 2019). In this context, our results demonstrated that O 3 exposure had a significant effect on the regulation of the expression of certain adipokines and metabolic proteins that are linked to metabolic disease (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive investigation about O 3 -related pathophysiological sequelae clearly show that exposure to this pollutant causes and exacerbates respiratory (D’Amato et al 2019; Manisalidis et al 2020; Sokolowska et al 2019) and cardiovascular diseases (Bourdrel et al 2017; Manisalidis et al 2020; Song et al 2020). What is more, O 3 exposure could also increase the incidence of chronic metabolic disorders, obesity and diabetes type II (Shore 2019; Thomson et al 2018), which has become one of the greatest global health threats of the 21st century. Furthermore, in humans, this pollutant increases the release of stress hormones, cortisol or rodent corticosterone (Thomson et al 2018), and alters the metabolic and endocrine response to the glucose challenge, which could also contribute to metabolic dysregulation (Thomson et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…O 3 exposure-released adrenal-derived stress hormones (e.g., epinephrine and corticosterone) disrupted lipid and carbohydrate metabolism, leading to hyperglycemia, glucose intolerance, and lung injury in rats [ 61 , 62 ]. Further rodent studies demonstrated that obesity augmented acute O 3 -induced airway hyperresponsiveness and inflammation [ 63 , 64 , 65 ], and diabetes caused early and exacerbated lung inflammation and fibrotic changes in response to subchronic O 3 (0.5 ppm, 4 h/day for 13 weeks) [ 10 ]. Epidemiological studies also showed a positive association between O 3 exposure and adult insulin resistance and preexisting lipid disorders and metabolic conditions (e.g., obesity and diabetes) [ 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 Air pollutants are known to cause inflammatory changes in respiratory epithelium and the impact of ambient air pollution on CRS pathogenesis and progression has recently been receiving increasing attention. [4][5][6][7][8][9][10][11] However, to our knowledge, the association between common air pollutants and sinonasal histopathology in CRS patients have not been studied thus far.…”
Section: Introductionmentioning
confidence: 99%